Comparación de los criterios SIRS y puntuación qSOFA en la aproximación diagnóstica de sepsis en pacientes adultos hospitalizados - Lecca-Zavaleta, José Luis (2019)
OBJECTIVE. To compare the frequency of hospitalized adult patients categorized as sepsis using SIRS criteria and qSOFA score. MATERIALS AND METHODS. Prospective, cross-sectional descriptive study. We reviewed 290 clinical records of adult patients hospitalized outside the ICU with suspicion or diagnosis of infection in the Medicine and Surgery services of the Regional Teaching Hospital of Trujillo, Peru, from August 2016 - January 2017, in whom the SIRS criteria and the qSOFA score were applied; we found the frequency of those who met 2 or more criteria of these scales and compared it with McNemar's nonparametric statistical test with significance of 5 % (p < 0,05). RESULTS. Average age of patients was 54,8 years (SD = 22,2), 49% male patients 51 % female patients; patients with 2 or more SIRS criteria were 37,58 % and with 2 or more criteria qSOFA were 24,14 %, finding a significant difference between the two (p < 0,001). CONCLUSION. The use of the SIRS criteria allows a diagnostic approach of sepsis more frequently in adult patients hospitalized for infection compared to the qSOFA score.